2006
DOI: 10.1158/1078-0432.ccr-05-1547
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Toxicity and Superior Therapeutic Activity of a Mitomycin C Lipid-Based Prodrug Incorporated in Pegylated Liposomes

Abstract: Purpose: A lipid-based prodrug of mitomycin C [MMC; 2,3-(distearoyloxy)propane-1-dithio-4V-benzyloxycarbonyl-MMC] was designed for liposome formulation. The purpose of this study was to examine the in vitro cytotoxicity, pharmacokinetics, in vivo toxicity, and in vivo antitumor activity of this new lipid-based prodrug formulated in polyethylene glycol^coated (pegylated) liposomes. Experimental Design: MMC was released from the MMC lipid^based prodrug (MLP) by thiolytic-induced cleavage with a variety of thiol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 35 publications
4
92
0
Order By: Relevance
“…9). The superior efficacy of these liposomes compared to the free parent drug, free Dox and Doxil ® has been demonstrated in vivo on mice bearing MDR murine lung carcinoma (M109R) [94], and resistant human ovarian carcinoma (A2780/AD) [95]. Further studies on subcutaneous models of gastric (N87), colon (HCT15) and pancreatic (Panc1) carcinoma confirmed the greater efficacy compared to standard treatments (i.e., irinotecan and Gem).…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…9). The superior efficacy of these liposomes compared to the free parent drug, free Dox and Doxil ® has been demonstrated in vivo on mice bearing MDR murine lung carcinoma (M109R) [94], and resistant human ovarian carcinoma (A2780/AD) [95]. Further studies on subcutaneous models of gastric (N87), colon (HCT15) and pancreatic (Panc1) carcinoma confirmed the greater efficacy compared to standard treatments (i.e., irinotecan and Gem).…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…DOI: 10.3109/10717544.2016.1145306 toxicological properties, such as organ targeting, increased efficacy, reduced toxicity, from bulk material of the same composition due to their nanoscale size (Gabizon et al, 2006;Ellis-Behnke et al, 2007;Kim, 2007). Whereas the larger micelles with the size range of 50-100 nm were removed by the liver and spleen, polymeric micelles smaller than 5 and 5-10 nm were easily eliminated through the renal glomeruli (Kedar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and preclinical studies have shown that the toxicity of PEGylated liposomal agents and other nontargeted nanoparticles carriers is less than the comparative small molecule (3,36,37). For example, the cytotoxicity of mitomycin C was drastically reduced when prepared in PEGylated liposomes (38). It also has been clinically noted that the biodistribution pattern of liposomes can lead to a relative reduction of drug concentrations in tissues that are known to be sensitive to the drug (39).…”
Section: Discussionmentioning
confidence: 99%